Difference between revisions of "022 Exam 1 Sample A, Problem 2"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span style="font-size:135%"><font face=Times Roman>2. Use implicit differentiation to find <math style="vertical-align: -16%">dy/dx</math> at the point <math style="vertical-...")
 
 
(7 intermediate revisions by the same user not shown)
Line 5: Line 5:
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|When we use implicit differentiation, we combine the chain rule with the fact that <math style="vertical-align: -18%">y</math> is a function of <math style="vertical-align: 0%">x</math>, and could really be written as <math style="vertical-align: -25%">y(x).</math> Because of this, the derivative with respect to <math style="vertical-align: 0%">x</math> of <math style="vertical-align:-24%">y^3</math> requires the chain rule, so  
+
|When we use implicit differentiation, we combine the chain rule with the fact that <math style="vertical-align: -18%">y</math> is a function of <math style="vertical-align: 0%">x</math>, and could really be written as <math style="vertical-align: -21%">y(x).</math> Because of this, the derivative of <math style="vertical-align:-17%">y^3</math> with respect to <math style="vertical-align: 0%">x</math> requires the chain rule, so  
 
|-
 
|-
|&nbsp;&nbsp;&nbsp;&nbsp; <math>\frac{d}{dx}\left(y^{3}\right)=3y^{2}\cdot\frac{dy}{dt}.</math>
+
|&nbsp;&nbsp;&nbsp;&nbsp; <math>\frac{d}{dx}\left(y^{3}\right)=3y^{2}\cdot\frac{dy}{dx}.</math>
 
|}
 
|}
  
Line 15: Line 15:
 
!Step 1: &nbsp;
 
!Step 1: &nbsp;
 
|-
 
|-
|First, we differentiate each term separately with respect to x to find that&thinsp; <math style="vertical-align: -18%">x^{3}-y^{3}-y=x</math> &thinsp;differentiates implicitly to
+
|First, we differentiate each term separately with respect to <math style="vertical-align: 0%">x</math> to find that&thinsp; <math style="vertical-align: -18%">x^{3}-y^{3}-y=x</math> &thinsp;differentiates implicitly to
 
|-
 
|-
 
|&nbsp;&nbsp;&nbsp;&nbsp; <math>3x^{2}-3y^{2}\cdot\frac{dy}{dx}-\frac{dy}{dx}=1</math>.
 
|&nbsp;&nbsp;&nbsp;&nbsp; <math>3x^{2}-3y^{2}\cdot\frac{dy}{dx}-\frac{dy}{dx}=1</math>.
Line 29: Line 29:
 
|}
 
|}
  
 +
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Final Answer: &nbsp;
 +
|-
 +
|&nbsp;&nbsp;&nbsp;&nbsp; <math style="vertical-align:-24%">dy/dx=2.</math>
 +
|}
 
[[022_Exam_1_Sample_A|'''<u>Return to Sample Exam</u>''']]
 
[[022_Exam_1_Sample_A|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 13:48, 17 April 2017

2. Use implicit differentiation to find at the point on the curve defined by .

Foundations:  
When we use implicit differentiation, we combine the chain rule with the fact that is a function of , and could really be written as Because of this, the derivative of with respect to requires the chain rule, so
    

 Solution:

Step 1:  
First, we differentiate each term separately with respect to to find that   differentiates implicitly to
     .
Step 2:  
Since they don't ask for a general expression of , but rather a particular value at a particular point, we can plug in the values and  to find
    
which is equivalent to . This solves to
Final Answer:  
    

Return to Sample Exam